2017
DOI: 10.1007/s11065-017-9347-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Measures in the Arab World: A Systematic Review

Abstract: Although Arabic is one of the most widely used languages in the world, little is known on the availability of standardized neuropsychological tests in Arabic. We review the literature published before 2016, using the keywords Arab*, cogniti*, and neuropsycholo*, as well as keywords for each Arab country. PubMed, PsycINFO, Education Source, Academic Search Complete, Education Resources Information Center, Shamaa, and Arabpsynet databases were searched, in addition to a selected number of Arabic medical and educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 86 publications
3
30
0
2
Order By: Relevance
“…Inhabitants of the Arab world are 370 million, in addition to eight million Arab immigrants living outside their country of origin [20]. Egypt's population alone makes up 23.6% of the Arabic-speaking population, and although Arabic is the fourth most commonly spoken language in the world [21], the availability of standardized neuropsychological tests in Arabic is scarce. This gives rise to the need of developing valid neuropsychological tests for these populations [22].…”
Section: Introductionmentioning
confidence: 99%
“…Inhabitants of the Arab world are 370 million, in addition to eight million Arab immigrants living outside their country of origin [20]. Egypt's population alone makes up 23.6% of the Arabic-speaking population, and although Arabic is the fourth most commonly spoken language in the world [21], the availability of standardized neuropsychological tests in Arabic is scarce. This gives rise to the need of developing valid neuropsychological tests for these populations [22].…”
Section: Introductionmentioning
confidence: 99%
“…As one example, Egypt has been at the forefront developing standardized Arabic evaluations, beginning as early as the 1920s (led by El-Kabbani) and extending into commonly used batteries developed in other cultures (e.g., Halstead-Retain and Luria-Nebraska;Al-Joudi, 2015). A recent review by Fasfous, Al-Joudi, Puente, and Perez-Garcia (2017) identified that, (Fasfous et al, 2017). Other efforts to develop normative standards outside of American and European cultures suggest comparability of the construct measured when normative standardizations and underlying issues of cultural validity are appropriately addressed (e.g., Zambia, Hestad et al, 2016, Kabula et al, 2017China, Gupta et al, 2014, Heaton et al, 2008, Shi et al, 2015Brazil, de Almeida, et al, 2013;India, Ghate et al, 2015, Kamat et al, 2012, Malda, van de Vijver, Srinivasan, Transler, & Sukumar, 2010Czech Republic, Bezdicek et al, 2012South Africa, Nell, 1999;Nell, Myers, Colvin, & Rees, 1994;Cameroon, Ruffieux, et al, 2010;South Korea, Ko, Rosen, Simpson, & Brown, 2014), although there are some exceptions (e.g., lexical fluency and block design in Cameroon, Ruffieux, et al, 2010).…”
Section: Cultural and International Considerationsmentioning
confidence: 99%
“…Although Arabic is one of the most widely used languages worldwide, little is known regarding the standardized neuropsychological tests available in Arabic [1]. One of the most widely used assessment packages in dementia is the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) which was established in 1986.…”
Section: Introductionmentioning
confidence: 99%